Combining Photothermal Therapy‐Induced Immunogenic Cell Death and Hypoxia Relief‐Benefited M1‐Phenotype Macrophage Polarization for Cancer Immunotherapy. Issue 2 (13th November 2020) - Zhou, Min; Wang, Xiaoyu; Lin, Shichao; Liu, Yufeng; Lin, Junshu; Jiang, Bo; Zhao, Xiaozhi; Wei, Hui
Abstract: The promise of anti‐tumor immunotherapy is limited partially by low antigen exposure and the hypoxic tumor microenvironment. To address these two limitations simultaneously, herein, a multifunctional AuNR@BSA/MnO2 to enable photothermal therapy‐induced immunogenic cell death (ICD) and hypoxia relief‐benefited M1 polarization of macrophages for enhanced cancer immunotherapy, is designed. The ICD and M1 polarization are demonstrated both in vitro and in vivo by detecting the corresponding markers. Then, enhanced immunotherapeutic efficacy is achieved in a 4T1 tumor‐bearing mice model. Additionally, when combined with a checkpoint blockade therapy (PD‐1 inhibitor), the AuNR@BSA/MnO2 shows distant effects including anti‐distant tumor, anti‐metastasis, and even improved survival. Last, the AuNR@BSA/MnO2 has multi‐imaging functions, such as photoacoustic imaging and magnetic resonance imaging. This study provides a new strategy to design multifunctional nanomedicines for improving anti‐tumor immunotherapy and imaging guided therapy. Abstract : A multifunctional AuNR@BSA/MnO2 is designed for tumor therapy, which enables photothermal therapy‐induced immunogenic cell death and hypoxia relief‐benefited M1 polarization of macrophages for enhanced cancer immunotherapy. An enhanced immunotherapeutic efficacy is achieved in 4T1 tumor‐bearing mice. Even distant effects are exhibited when combined with a checkpoint blockade therapy.